Candida albicans mannans mediate Streptococcus mutans exoenzyme GtfB binding to modulate cross-kingdom biofilm development in vivo. - Geelsu Hwang; Yuan Liu; Dongyeop Kim; Yong Li; Damian J Krysan; Hyun Koo (PLoS Pathogens)
Candida albicans is frequently detected with heavy infection by Streptococcus mutans in plaque-biofilms from children with early-childhood caries (ECC). This cross-kingdom biofilm contains an extensive matrix of extracellular α-glucans that is produced by an exoenzyme (GtfB) secreted by S. mutans. Here, we report that mannans located on the outer surface of C. albicans cell-wall mediates GtfB binding, enhancing glucan-matrix production and modulating bacterial-fungal association within biofilms formed in vivo. Using single-molecule atomic force microscopy, we determined that GtfB binds with remarkable affinity to mannans and to the C. albicans surface, forming a highly stable and strong bond (1-2 nN). However, GtfB binding properties to C. albicans was compromised in strains defective in O-mannan (pmt4ΔΔ) or N-mannan outer chain (och1ΔΔ). In particular, the binding strength of GtfB on och1ΔΔ strain was severely disrupted (>3-fold reduction vs. parental strain). In turn, the GtfB amount on the fungal surface was significantly reduced, and the ability of C. albicans mutant strains to develop mixed-species biofilms with S. mutans was impaired. This phenotype was independent of hyphae or established fungal-biofilm regulators (EFG1, BCR1). Notably, the mechanical stability of the defective biofilms was weakened, resulting in near complete biomass removal by shear forces. In addition, these in vitro findings were confirmed in vivo using a rodent biofilm model. Specifically, we observed that C. albicans och1ΔΔ was unable to form cross-kingdom biofilms on the tooth surface of rats co-infected with S. mutans. Likewise, co-infection with S. mutans defective in GtfB was also incapable of forming mixed-species biofilms. Taken together, the data support a mechanism whereby S. mutans-secreted GtfB binds to the mannan layer of C. albicans to promote extracellular matrix formation and their co-existence within biofilms. Enhanced understanding of GtfB-Candida interactions may provide new perspectives for devising effective therapies to disrupt this cross-kingdom relationship associated with an important childhood oral disease.